2014
DOI: 10.1016/j.renene.2013.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of low grade iron ore pellet using palm kernel shell

Abstract: Effective use of local iron ore and biomass waste as energy and material resources in iron making is an interesting economic prospect since Malaysia imports iron ore to supply its domestic steel consumption while there is an abundance of biomass waste from the palm oil industry. In this work, a composite pellet made of Malaysian iron ore with palm kernel shell (PKS) waste was subjected to reduction tests using an electric tube furnace to investigate the effect of temperature and PKS content on reduction rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 16 publications
3
26
0
2
Order By: Relevance
“…[13][14][15][16] This process provides an advanced utilization opportunity for the high volatile coals as well as biomass materials. [17][18][19][20][21][22][23][24][25][26][27][28] Gupta et al 17) have investigated the behavior of water hyacinth char addition in iron ore pellet. The results shown that the biomass char could be a potential for making iron ore pellet.…”
Section: Experiments and Kinetic Modeling For Reduction Of Ferric Oximentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] This process provides an advanced utilization opportunity for the high volatile coals as well as biomass materials. [17][18][19][20][21][22][23][24][25][26][27][28] Gupta et al 17) have investigated the behavior of water hyacinth char addition in iron ore pellet. The results shown that the biomass char could be a potential for making iron ore pellet.…”
Section: Experiments and Kinetic Modeling For Reduction Of Ferric Oximentioning
confidence: 99%
“…Hayashi et al 23) compared different carbothermic reductions of hematite and magnetite powders under the condition of microwave heating and analyzed different procedures. Rashid et al 24) investigated the utilization of low grade iron ore and palm kernel shell (PKS) waste biomass as an alternative energy source in ironmaking. The results showed that iron oxide in iron ore could be fully reduced to magnetite and partially to wustite when up to 30 wt.% of PKS was present in the mixture.…”
Section: Experiments and Kinetic Modeling For Reduction Of Ferric Oximentioning
confidence: 99%
“…There are several methods which can be used in iron and steel industries to minimize CO 2 emissions. A promising solution is the use renewable energy resources, such as biomass as the reducing agent in the existing iron production process to replace fossil fuels such as coke and coal [9]. Biomass is a widely distributed, abundant, renewable, and environment friendly reducing agent that has attracted the attention of international scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…As biomass has superior properties, the reduction of metallic oxides was mainly performed either using biomass in their natural form or char from biomass pyrolysis. [4][5][6] One of the adverse consequences is the ash from the biomass will be retained in the iron products, which requires subsequent magnetic separation. Furthermore, the reduction process was driven by the carbon-thermic Boudouard reaction.…”
Section: Introductionmentioning
confidence: 99%